On the influence of rock glacier dynamics on the runoff in basin of the Ulken Almaty (Bolshaya Almatinka) River, Northern Tien Shan - L. S. Lebedeva; V. P. Kapitsa; Z. D. Takibaev; V. V. Goncharenko; V. M. Lytkin; A. N. Kamalbekova (Лëд и снег, 2024)
The purpose of the work was to study the dynamics of mountain stone glaciers and streams flowing down from them for an understanding their hydrological significance. Two glaciers: Morenny and Gorodetsky, were analyzed, both located in the river Ulken Almaty (Big Almatinka) basin, Northern Tien Shan. On the average, the rate of surface displacement of the Morennoye glacier is higher than that of the Gorodetsky, which is associated with increased ice content of the last one. The increase in rates of surface displacement of both stone glaciers revealed in 2021–2022 when compared to previous years turned out to be consistent with the widely discussed idea of intensification of such glaciers dynamics under the present-day climate changes and glacier retreats. It was found that the stone glaciers have a pronounced influence on the water regime, temperature and chemical composition of watercourses formed by water running out from them. They are distinguished by the almost complete absence of intraday fluctuations in the level, temperature, and specific electrical conductivity of water, which are more pronounced in rivers and streams with glacial alimentation during the summer time. Some waterflows from the Gorodetsky glacier do not freeze in winter, which is indicative of significant groundwater reserves in its body. The waters of each of the above stone glaciers differ in their characteristic mineralization, temperature, and the ratio of the major ions. The stable water flow from such glaciers can play an important role in maintaining a river runoff during periods of the low stream discharge.